التنوير الألماني وأهم مفكريه - نوفل، وضاح حسين (جامعة دمشق, 2022)
أشرقت شمس التنوير في أوروبا في القرن الثامن عشر فأضاءت العقول ودفعت بالعلم والمعرفة قدما، وكان التنوير الألماني ومفكريه علامة فارقة في هذا العصر، فلا نستطيع أن نتصور عصر التنوير بدون المفكرين والفلاسفة الألمان هؤلاء المبدعين الذين دعوا إلى النقد وإعمال دور العقل في كل شيء وإلى التسامح الديني والابتعاد عن الأحكام المسبقة، وكان شعار التنوير كما عرفه ايمانويل كانت "تشجع لتعرف" هذا التعريف الشهير الذي قلب المعايير ودفع لتغيير شمل كل نواحي الحياة وغير نظرة الإنسان لكل ما هو موجود. وأضاء مفكري عصر التنيور الألماني مثل ليسينغ وغيللرت وغوتشد وليشتنبيرغ سماء العلم والمعرفة وكانت أعمالهم الفكرية كنزا ثمينا للبشرية. اتبع البحث المنهج العلمي التاريخي التحليلي من خلال جمع المادة العلمية بالتركيز على المصادر والمراجع الألمانية، وإخضاع هذه المعلومات للمقارنة والتحليل وإعادة التركيب. The sun of enlightenment rose in Europe in the eighteenth century, illuminating minds and pushing science and knowledge forward. The German Enlightenment and its intellectuals were a milestone in this era. Furthermore, the Enlightenment era cannot be perceived without those creative German thinkers and philosophers who called for: criticism, realization of the role of reason, religious tolerance, and avoidance of preconceptions. Moreover, '' Be encouraged to know'' was the slogan of the Enlightenment as being defined by Immanuel Kant. This famous definition had overturned the standards and prompted a change in all aspects of life, as well as it changed the human view of everything that exists. German Enlightenment thinkers such as: Lessing, Gellert, Gottschad and Lichtenberg illuminated the sky of science and knowledge, and their intellectual works were a precious treasure for mankind. This research followed the historical-analytical scientific approach through collecting the scientific material focusing on German sources and references, and subjecting this information to comparison, analysis and restructuring.
Keywords: عصر التنوير -- الحركات الفكرية -- التربية الأخلاقية -- التسامح الديني -- المفكرون الألمان